Orodispersible Thin Film: A new patient-centered innovation - Gupta, Maram Suresh; Kumar, Tegginamath Pramod; Gowda, Devegowda Vishakante (Journal of drug delivery science and technology, 2020)
Orodispersible Thin Films (OTFs) are the most innovative and patient-centered novel drug delivery systems. Many Pharmaceutical companies and academic experts across the world are already in the process of exploring the true potential of these films in delivering drugs not only from synthetic sources but also from the natural sources. The beauty of this unique drug delivery system is that they don't need water for consumption, as we see with consumption of conventional dosage forms (tablets, capsules), by the subjects. Additionally, these delivery systems are excellent in gaining patient compliance in general and particularly in pediatric and geriatric patient population. The present review provides insight into the history of OTFs, definitions, types of classification, mandatory characteristics, formulation aspects, manufacturing and evaluation methodologies, stability, approvals by regulatory authorities (CDSCO of India), key players in the domain, notable patent battle and future market potential. [Display omitted]